Sound propagation in Megaichnus major (paleoburrows) as evidence of acoustic communication of fossorian Mylodontoidea. - Munhoz, Marcelo Schereiber [UNESP]; Audi, Caroline [UNESP]; Buchmann, Francisco Sekiguchi [UNESP] (Sociedade Brasileira de Paleontologia, 2024)
Megaichnus major are natural underground structures attributed to the folivoran Xenarthra (giant sloths), represented by tunnels and halls excavated during the Pliocene and Pleistocene. There is evidence of gregarious behavior in Mylodontidae, making it necessary to estimate sound propagation within the tunnels. Estimates based on the middle ear of Lestodon sp. and Glossotherium robustum put an auditory frequency range from 44 Hz to 16,490 Hz. This work describes sound propagation experiments within M. major at various frequencies and distances from the ground. The experiment took place in the Megaichnus major (URU-01-P2) in coordinates-27o 57’ 54,7’’S,-49o 30’ 33,2’’W, a set of tunnels, trenches and sinkholes, at an altitude of 1,036m, in the Municipality of Urubici, Santa Catarina, Brazil. A well-preserved tunnel URU-01-P2 was chosen, with an elliptical section, without sediment filling, roof collapse or floor erosion. Pure tones were generated at frequencies of 100 Hz, 600 Hz, 1,700 Hz, 2,300 Hz, 15,300 Hz, and 16,500 Hz; with constant intensity level of 65 dB SPL. With a decibel meter, the intensity level was measured in dB SPL from the sound source at distances of 3 m, 6 m, 9 m and at heights of 0.1 m, 1.2 m and 2 m. It was observed that there was reduced attenuation (2–3 dB SPL) at lower frequencies (100–600Hz) along the tunnel P2. Sound propagation near the ground was better considering the same distances at different heights. It was also noted that the geometry of the tunnels generated the “stethoscope effect”, the magnification of the sound intensity at certain frequencies. These frequencies, therefore, propagate with less attenuation in relation to those of higher ones, which would be more efficient for the communication of Mylodontidae in the fossorial environment.
PROPAGAÇÃO SONORA EM MEGAICHNUS MAJOR (PALEOTOCAS) COMO EVIDÊNCIA DE COMUNICAÇÃO ACÚSTICA DE MYLODONTOIDEA FOSSORIAIS
Keywords: Mylodontidae; paleoburrows; Rio dos Bugres; Urubici